An Empirical Analysis Of Debt-equity Choice In Indonesian Companies. - Santoso, Augustinus Setiawan" (2004)
This study offers new insights by employing Indonesian data. The uniqueness of Indonesian companies is reflected by the common occurrence of ownership concentration among a few large families and affiliation with a corporate group in which seems nonexistent in many developed countries. With regard to the methodology problem, this study uses simultaneous equations model to overcome the endogeneity problem in debt-equity study. It is reported that the external block ownership has dominant position by having majority control and impact on powerless Indonesian managers. The inadequate legal framework for investors' protection, insufficient internal financing and improper development of the capital market occur. With regard to this situation, debt-equity choice was widely practiced. There is evidence that Indonesian companies relied heavily on loans to finance unrealistic rapid corporate expansion. The insignificant relationship between the level of debt and tangibility of assets and profitability indicate the appearance of moral hazard problem before the crisis